In Vivo Characterization of Cortical and White Matter Microstructural Pathology in Growth Hormone-Secreting Pituitary Adenoma - Yuan, Taoyang; Ying, Jianyou; Li, Chuzhong; Jin, Lu; Kang, Jie; Shi, Yuanyu; Gui, Songbai; Liu, Chunhui; Wang, Rui; Zuo, Zhentao; Zhang, Yazhuo (Frontiers in Oncology, 2021)
Background The growth hormone (GH) and insulin-like-growth factor 1 (IGF-1) axis has long been recognized for its critical role in brain growth, development. This study was designed to investigate microstructural pathology in the cortex and white matter in growth hormone-secreting pituitary adenoma, which characterized by excessive secretion of GH and IGF-1. Methods 29 patients with growth hormone-secreting pituitary adenoma (acromegaly) and 31 patients with non-functional pituitary adenoma as controls were recruited and assessed using neuropsychological test, surface-based morphometry, T1/T2-weighted myelin-sensitive magnetic resonance imaging, neurite orientation dispersion and density imaging, and diffusion tensor imaging. Results Compared to controls, we found 1) acromegaly had significantly increased cortical thickness throughout the bilateral cortex (pFDR < 0.05). 2) T1/T2-weighted ratio in the cortex were decreased in the bilateral occipital cortex and pre/postcentral central gyri but increased in the bilateral fusiform, insular, and superior temporal gyri in acromegaly (pFDR < 0.05). 3) T1/T2-weighted ratio were decreased in most bundles, and only a few areas showed increases in acromegaly (pFDR < 0.05). 4) Neurite density index (NDI) was significantly lower throughout the cortex and bundles in acromegaly (pTFCE < 0.05). 5) lower fractional anisotropy (FA) and higher mean diffusivity (MD), axial diffusivity (AD) and radial diffusivity (RD) in extensive bundles in acromegaly (pTFCE < 0.05). 6) microstructural pathology in the cortex and white matter were associated with neuropsychological dysfunction in acromegaly. Conclusions Our findings suggested that long-term persistent and excess serum GH/IGF-1 levels alter the microstructure in the cortex and white matter in acromegaly, which may be responsible for neuropsychological dysfunction.